(untitled) (Collaborate Engineering Daily Book Series, 2025)
The development of non-conventional energy is one of the main strategies in dealing with the global energy crisis and climate change. Energies such as solar, wind, biomass, and marine energy are promoted as more environmentally friendly alternatives to fossil energy. However, behind this positive image, there are various social conflicts and environmental challenges that are often overlooked in the implementation process. This perspective article aims to critically examine the dynamics of social conflict and environmental impacts that arise from the construction of non-conventional energy projects. The method used is a qualitative approach through literature study and conceptual analysis. The results of the discussion show that social conflicts are generally related to land issues, community participation, and inequality in the distribution of economic benefits. Meanwhile, from the environmental side, non-conventional energy development can trigger ecosystem disturbances, changes in land use, and uncertainty of long-term impacts. Therefore, a more inclusive, ecosystem-based, and social justice-oriented approach to development is needed so that the energy transition can run sustainably.